МЕЖДУ СМЕРТЬЮ И БЕССМЕРТИЕМ. ПРОБЛЕМА ГЕРОЯ В НОВЕЛЛАХ ЭДВАРДА КОЦБЕКА «СТРАХ И МУЖЕСТВО» (Филолошки студии, 2019)
On the background of the tragedy of the Second world war Kocbek shows the hardest internal struggle happening in the hero's soul. Actively using the heritage of the Slovene and allEuropean poetic, prosaic and musical national culture, the writer emphasizes not exclusiveness, but more likely validity of occurrence of internal spiritual division of the person, his contemporary. In the book «Fear and courage» with new sincerity the author creates a poetic image of human existention, full of conflicts and contradictions, freedom and responsibility, defined by physical death and spiritual immortality.